Quantitative modelling of seismic site amplification in an earthquake-endangered capital city: Bucharest, Romania - Bala, Andrei (Natural hazards (Dordrecht), 2014)
Bucharest, the capital city of Romania, with more than 2 million inhabitants, is considered as a natural disaster hotspot by a recent global study of the World Bank and the Columbia University (Dilley M et al. Natural disaster hotspots: a global risk analysis. International Bank for Reconstruction and Development/The World Bank and Columbia University, Washington, DC in 2005 ). Therefore, it is classified as the second metropolis in Europe, after Istanbul, subjected to important losses in the case of a destructive Vrancea earthquake with moment magnitude greater than seven. Four major earthquakes with moment magnitudes between 6.9 and 7.7 hit Bucharest in the last 68 years. The most recent destructive earthquake on March 4, 1977, with a moment magnitude of 7.4, caused about 1,500 casualties in the capital alone. All disastrous intermediate-depth earthquakes are generated within a small epicentral area—the Vrancea seismogenic region—about 150 km northeast of Bucharest. Thick unconsolidated sedimentary layers below Bucharest amplify the arriving seismic waves causing severe destruction. Ten 50-m-deep boreholes are drilled in the metropolitan area of Bucharest in order to obtain a unique, homogeneous dataset of seismic, soil-mechanic and elasto-dynamic parameters. Cores for dynamic tests were extracted, and vertical seismic profiles were performed to obtain an updated site amplification model related to earthquakes waves. The boreholes are placed near former or existing seismic station sites to allow a direct comparison and calibration of the borehole data with previous seismological measurements. A database containing geological characteristics for each sedimentary layer, geotechnical parameters measured on rock samples, P- and S wave velocity and density for each sedimentary layer is set up, as a result of previous papers with this subject. Direct data obtained by the geophysical methods in the new boreholes drilled in Bucharest City, as well as from laboratory measurements, are used as input data in the program SHAKE2000. Results are obtained in the form of spectral acceleration response, and peak acceleration in depth is computed for every site in which in situ measurements were performed. The acceleration response spectra correspond to the shear-wave amplifications due to the models of sedimentary layers down to (a) 50 m depth; (b) 70 m depth; and (c) 100 m depth. A comparison of the acceleration response spectra obtained by modelling at surface with a real signal recorded at surface is obtained in three sites, as test sites for the three depths considered, in order to calibrate the results obtained by equivalent linear method of the seismic site response.